The Concept of Prophetic Education According to Imam Tirmidzi in the Book of Syamail Muhammadiyah - Muhammad Rifki Sofa Izurrohman; Mohammad Zakki Azani; Hakimuddin Salim (Walidem Institute and Publishing, 2023)
Prophetic education is education that imitates the life of the prophet. departs from the prophetic sentence (prophecy or relating to the prophet), which then makes the notion of education to form productive human beings and can build a pious civilization, or it can also be interpreted as education which prioritizes and interprets all the behaviour of the prophet, namely the Prophet Muhammad SAW. The Saheeh, Sunan, Musnad and others reveal these beautiful qualities and great morals. Likewise comes in a separate explanation, one of the well-known books is the book Syamail Muhammadiyah which was written by Imam Tirmidhi, the author of the book al-jami' who died in 279H. Being a big and important reference in the theme, and has helped many hadith scholars know the personality and morals of the Prophet. The research that utilizes the scientific work (book) of one of the scholars who lived and preached in the 2nd century of Islam uses the library research method, by making the theological approach the main goal, namely to make his people more familiar with and follow what has been taught. in their daily interactions. As for some conclusions that can be drawn from this research is to humanize humans according to perfunctory levels guided, directed, and exemplified by the Prophet. In other words, prophetic education aims to realize humans as servants of Allah who can worship Him with good thoughts, deeds and even feelings. Likewise, humans as actors who are ready to act, not as products that are ready to be used in institutions, factories, offices or other things, because human beings are essentially not working machines. Hopefully with this research, humans from now until the end of time can interpret, practice and place their position as perfect humans (kaffah).